A study on evaluating of the effectiveness on implementation environmental management system (EMS) for the operation & management control at palm oil mill waste treatment plant system / Ahmad Sharim Abdullah - Abdullah, Ahmad Sharim (2007)
Palm oil industry has become one of the rapidly growing sectors in Malaysia. Regarding such expansion, the levels of pollution generated from the industry have been escalating. Besides, the drawback mainly found is surface water pollution which is consequential of either insufficient or improper disposal of wastewater and solid wastes. The wastes generated have significant impact on the environment if not properly managed. That is how the environmental management system comes as a bottom line to organize and as the guidelines to manage all activity on the operation to avoiding the pollution and to improve the environmental management. This study is focus to effectiveness to an organization by implementation the environmental management system for the management and operation control at waste treatment plant operation. For the more understanding on this study, the details literature review on waste treatment plant process in palm oil mill, environmental management system and pollution control are discussed clearly before detail discussion on case study selected.